1991
DOI: 10.1093/jnci/83.5.355
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothesis: Nonsteroidal Anti-Inflammatory Drugs Reduce the Incidence of Large-Bowel Cancer

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit prostaglandin synthesis and tumor growth in the rodent colon. We assessed NSAID use in relation to risk of human large-bowel cancer in a hospital-based, case-control study of 1326 patients with colorectal cancer and 4891 control patients. For regular NSAID use that continued into the year before interview, the multivariate relative risk estimate was 0.5 (95% confidence interval, 0.4 to 0.8); the estimate decreased as the duration of use increased, but the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
138
0
3

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(150 citation statements)
references
References 12 publications
9
138
0
3
Order By: Relevance
“…There is substantial evidence of an inverse association between use of nonsteroidal anti-inflammatory drugs (NSAIDs) and the risk of colorectal cancer (Kune et al, 1988;Rosenberg et al, 1991Rosenberg et al, , 1998Thun et al, 1991Thun et al, , 1993Suh et al, 1993;Muscat et al, 1994;Peleg et al, 1994;Schreinemachers et al, 1994;Giovannucci et al, 1995;Smalley et al, 1999;Baron and Sandler, 2000;Coogan et al, 2000;Langman et al, 2000;Rodrigues and Huerta-Alvarez, 2001). A protective effect was initially observed in experimental studies and has been seen in epidemiologic studies of both cohort and casecontrol designs.…”
mentioning
confidence: 99%
“…There is substantial evidence of an inverse association between use of nonsteroidal anti-inflammatory drugs (NSAIDs) and the risk of colorectal cancer (Kune et al, 1988;Rosenberg et al, 1991Rosenberg et al, , 1998Thun et al, 1991Thun et al, , 1993Suh et al, 1993;Muscat et al, 1994;Peleg et al, 1994;Schreinemachers et al, 1994;Giovannucci et al, 1995;Smalley et al, 1999;Baron and Sandler, 2000;Coogan et al, 2000;Langman et al, 2000;Rodrigues and Huerta-Alvarez, 2001). A protective effect was initially observed in experimental studies and has been seen in epidemiologic studies of both cohort and casecontrol designs.…”
mentioning
confidence: 99%
“…One study (Rosenberg et al, 1991) was excluded from the analysis because of lack of data on the estimator of relative risk. The remaining studies were 6 cohort studies (Table 1) and 8 case-control studies ( Table 2).…”
mentioning
confidence: 99%
“…Regular aspirin use was reported by only 47 (3.5%) cases and 77 (4.1%) control subjects, giving a multivariate odds ratio (OR) of 0.7 (95% Cl 0.5-1.0) after allowance for education, physical exercise and selected dietary factors.Keywords: aspirin; non-steroidal anti-inflammatory drugs; colorectal neoplasms; pharmacoepidemiology At least six case-control studies (Kune et al, 1988;Rosenberg et al, 1991;Suh et al, 1993;Muscat et al, 1994;Peleg et al, 1994), based on over 3700 cases, have suggested that the risk of colorectal cancer may be reduced in regular aspirin users. Likewise, four (Thun et al, 1991(Thun et al, , 1993Schreinemachers and Everson, 1994;Giovannucci et al, 1994Giovannucci et al, , 1995 out of five (Paganini-Hill et al, 1989;Paganini-Hill, 1994) (Paganini-Hill, 1994;Greenberg and Baron, 1996).…”
mentioning
confidence: 99%
“…At least six case-control studies (Kune et al, 1988;Rosenberg et al, 1991;Suh et al, 1993;Muscat et al, 1994;Peleg et al, 1994), based on over 3700 cases, have suggested that the risk of colorectal cancer may be reduced in regular aspirin users. Likewise, four (Thun et al, 1991(Thun et al, , 1993Schreinemachers and Everson, 1994;Giovannucci et al, 1994Giovannucci et al, , 1995 out of five (Paganini-Hill et al, 1989;Paganini-Hill, 1994) cohort studies showed a protection of between 20% and 40% among regular aspirin users, although in the American Nurses' Health Study (Giovannucci et al, 1995) the protection was only evident for frequent use (2 four times per week) and after 20 years of use.…”
mentioning
confidence: 99%